Novel pili-like surface structures of Halobacterium salinarum strain R1 are crucial for surface adhesion - Losensky, Gerald; Vidakovic, Lucia; Klingl, Andreas; Pfeifer, Felicitas; Fröls, Sabrina (Frontiers in Microbiology, 2015)
It was recently shown that haloarchaeal strains of different genera are able to adhere to surfaces and form surface-attached biofilms. However the surface structures mediating the adhesion were still unknown. We have identified a novel surface structure with Halobacterium salinarum strain R1, crucial for surface adhesion. Electron microscopic studies of surface-attached cells frequently showed pili-like surface structures of two different diameters that were irregularly distributed on the surface. The thinner filaments, 7 - 8 nm in diameter, represented a so far unobserved novel pili-like structure. Examination of the Hbt. salinarum R1 genome identified two putative gene loci (pil-1 and pil-2) encoding type IV pilus biogenesis complexes besides the archaellum encoding fla gene locus. Both pil-1 and pil-2 were expressed as transcriptional units, and the transcriptional start of pil-1 was identified. In silico analyses revealed that the pil-1 locus is present with other euryarchaeal genomes whereas the pil-2 is restricted to haloarchaea. Comparative real time qRT-PCR studies indicated that the general transcriptional activity was reduced in adherent versus planktonic cells. In contrast, the transcription of pilB1 and pilB2, encoding putative type IV pilus assembly ATPases, was induced in comparison to the archaella assembly/motor ATPase (flaI) and the ferredoxin gene. Mutant strains were constructed that incurred a flaI deletion or flaI/pilB1 gene deletions. The absence of flaI caused the loss of the archaella while the additional absence of pilB1 led to loss of the novel pili-like surface structures. The ΔflaI/ΔpilB1 double mutants showed a 10-fold reduction in surface adhesion compared to the parental strain. Since surface adhesion was not reduced with the non-archaellated ΔflaI mutants, the pil-1 filaments have a distinct function in the adhesion process.